New Dimensions of Public libraries in a post war development of the society - Arulanantham, S. (University of Keleniya, 2012)
The main focus of this article is to emphasize the role of public library sector in Northern Sri Lanka towards providing variety of services to the war- affected people seeking help in solving their problems. With the general introduction it tries to explain the environment in which the reading habit of the society flourished in each and every corner before the war, lists the the factors affecting the reading environment of present day society and finally suggests how the public libraries could act in various dimensions to fulfill the demand of high intensity of the services in the process of reconstructing a post-war society soon after a longstanding civil war and the corresponding efforts of rehabilitation of its members from the physical and emotional damages.
Keywords: Public library services; Social development